The Development of Kuih Escapade 3D Interactive PC Game Application - Tan, Wei Chin; Md. Fudzee, Mohd Farhan (Applied Information Technology And Computer Science, 2024)
The young generation nowadays is losing interest in preparing traditional kuih. Existing exploration video games lack local content, and interactive learning software or applications to promote awareness and understanding of traditional Malaysian kuih are limited. Therefore, the project aims to develop a 3D interactive PC game, “Kuih Escapade”, that provides players, specifically youth aged 15 to 25, with first-person perspective exploration gameplay for discovering various traditional kuih within the game’s virtual environment. This game also integrates hidden object gamification, storytelling and interactive in-game challenges to enhance the game experience and user engagement. Agile approach is chosen as the methodology for the entire project. Kuih Escapade has been successfully developed to be a fully functional interactive platform for users to explore the cultural heritage of traditional Malaysian kuih in a modern setting. By conducting user acceptance testing using the SUS format, Kuih Escapade has achieved all objectives and obtained a positive feedback result of 86.375%, indicating that the developed PC game application has met user expectations for both usability and user experience.